Hubungan Status Gizi Dengan Riwayat Hipertensi Pasien Lansia di RSUD Sawerigading Palopo (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Previous studies showed that most of the respondents who were hospitalized at Sawerigading Hospital, Palopo City were the elderly group, with mostly normal nutritional status and were treated with a diagnosis of hypertension. This study aims to determine the relationship of initial nutritional status with a history of hypertension in the elderly group who are hospitalized at Sawerigading Hospital, Palopo City. This research is a cross sectional study, which is a correlational study to find out whether there is a relationship between nutritional status variables and a history of hypertension in the elderly who are hospitalized. The data used is secondary data, the sample selection in this study was carried out using a purposive sampling technique with sample inclusion criteria, namely having data from anthropometric measurements, diagnoses or blood pressure measurements, and aged ≥ 60 years. The results showed that the total respondents aged ≥ 60 years were 195 people with the percentage of hypertension status mostly did not have history of hypertension 122 (62.6%) and most of them with normal nutritional status 116 people (59.5%). The results also show that there is no significant relationship between nutritional status and the incidence of hypertension in the elderly (p=0.284).